Feasibility and Acceptability of a High School Relationship Abuse and Sexual Assault Bystander Prevention Program: School Personnel and Student Perspectives - Edwards, Katie M. (Journal of interpersonal violence, 2021)
Relationship abuse (RA) and sexual assault (SA) are concerning issues for high school youth that occur at alarmingly high rates. Therefore, school-based prevention programs are often developed to try to mitigate these issues. The attitudinal and behavioral changes stemming from school-based intervention programs are often the primary focus of outcome research, but it is also important to identify program feasibility (e.g., dosage, adherence) and acceptability (e.g., likeability). The current study assessed the feasibility and acceptability of a high school classroom-based RA and SA intervention, Bringing in the Bystander–High School Curriculum (BITB-HSC); the BITB-HSC also includes a workshop and reading materials for school personnel and parents. Data were collected after the BITB-HSC was administered in high schools from students who participated in the program (N = 970) and school personnel who were exposed to some components of the BITB-HSC and provided feedback (N = 161). Results indicate that overall students were adherent to the BITB-HSC (e.g., attended sessions) and that the majority of students understood the information presented, thought the program was good, and liked the facilitators. School personnel data indicated that they were generally supportive of the program and found the school personnel workshop and handout helpful. These findings extend current knowledge regarding the implementation of school-based violence prevention programs and highlight the importance of research on program feasibility and acceptability when developing a program for large-scale dissemination.